Sistem Monitoring Suhu dan Kelembapan Pada Ruang Penyimpanan Roti Berbasis Internet Of Thing (IOT) - Khozainuz Zuhri; Ahmad Ihkwan; Fatimah Fahurian (Universitas Mitra Indonesia, 2021)
AbstractStorage is one of the security measures that aim to maintain and maintain product quality. In the bread storage room, for example, the quality of bread has been determined in the preparation of the bread dough ingredients and also the temperature and humidity of the room which must be maintained. The problem that often occurs is that the employee in charge of monitoring the room is constrained by the location of the distance between the storage room and the remote monitoring room, while data from room temperature and humidity must be reported to the monitoring officer to ensure the quality of the production material. One of the efforts to ease this problem is to build a real-time humidity and temperature monitoring system that makes it easier for employees to work in storage rooms remotely without having to come directly. One of the current technological developments is the IOT (Internet Of Things). The IOT concept can be used to make it easier for employees to monitor the temperature and humidity of storage space through web-based applications and android applications. Humidity and room temperature monitoring system application by working in accordance with the programming instruction sequence and monitoring system control using a user interface in the form of web-based applications and realtime android applications. The system application obtains temperature and humidity data from the server data which is then displayed on the interface so that it can be monitored in realtime.